2016
DOI: 10.1111/1460-6984.12282
|View full text |Cite
|
Sign up to set email alerts
|

Does the recording medium influence phonetic transcription of cleft palate speech?

Abstract: Phonetic transcription is influenced to some extent by visual cues. However, as long as age-appropriate articulatory and phonological simplification processes are scored as correct when evaluating consonant production in the speech of young children born with cleft palate using phonetic transcription, the recording medium does not seem to affect the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We chose to investigate CLP speech as it is particularly vulnerable to problems with interrater reliability due to covert errors and non-native phonetic realisations, and because it has been previously studied with a similar instrumental technique, namely electropalatography. In line with Klintö and Lohmander [16] adding an extra modality, in our case ultrasound, had little impact on the percentage of consonants recorded as correct. Both the audio-only (AO) and ultrasound-aided (UA) transcribers noted similar rates of both correct and in-error productions suggesting that both methods are valid for making decisions about overall severity of SSD or potentially for measuring outcomes after intervention.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We chose to investigate CLP speech as it is particularly vulnerable to problems with interrater reliability due to covert errors and non-native phonetic realisations, and because it has been previously studied with a similar instrumental technique, namely electropalatography. In line with Klintö and Lohmander [16] adding an extra modality, in our case ultrasound, had little impact on the percentage of consonants recorded as correct. Both the audio-only (AO) and ultrasound-aided (UA) transcribers noted similar rates of both correct and in-error productions suggesting that both methods are valid for making decisions about overall severity of SSD or potentially for measuring outcomes after intervention.…”
Section: Discussionsupporting
confidence: 82%
“…Accuracy of these transcriptions can be improved in several ways: audio and/or video recording the speech samples for careful and repeated listening; use of listeners familiar with the client group; use of multiple transcribers [15]; acoustic analysis; or instrumental articulatory techniques. A recent study by Klintö and Lohmander [16] showed that using of video-recordings of the face, rather than audio-recording only, improved intertranscriber reliability and resulted in identification of more errors in three-year-olds with CLP.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption was that this indicator would have a better interjudge percentage agreement if we used all 59 target consonants from SVANTE, 6 (10.2%) of which are /s/. The use of audio-video recordings for the ratings may also improve the agreement (Klintö and Lohmander, 2017). Calculations with κ showed better agreement than the point-by-point agreement.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, routine visits to the CLP team SLPs are audio-recorded for clinical purposes, and video recordings are not made on a regular basis. This probably led to lower interjudge percentage agreement for PCC than audio-video recordings would have produced (Klintö and Lohmander, 2017). Thus, it might have also influenced the reliability for the quality indicator proportion of children with ≥86% correct consonants .…”
Section: Discussionmentioning
confidence: 99%
“…Reliability can be improved through definitions of perceptual terms (Keuning et al, 1999), anchor stimuli (Eadie & Kapsner-Smith, 2011;Shrivastav, Sapienza, & Nandur, 2005), reference voices (Granqvist, 2003), standardization of the speech material (Klintö, Salameh, Svensson, & Lohmander, 2011), and recording medium (Klintö & Lohmander, 2017). Thus, methodological knowledge and skills training are crucial for reliable perceptual assessments.…”
Section: Introductionmentioning
confidence: 99%